Vogt Koyanagi Harada syndrome in a 15-year-old girl, steroids side effects and recurrences - Yıldırım, Gamze; Çavdarlı, Cemal; Özdemir, Emine Yıldız; Alp, Mehmet Numan (The Turkish Journal of Pediatrics, 2021)
Background. Vogt-Koyanagi-Harada Syndrome is rare in childhood and is usually seen between the 2nd and 5th decades. We present a 15-year-old girl with findings of incomplete Vogt-Koyanagi-Harada Syndrome. Case. In the first visit, anterior chamber inflammation, vitritis, serous retinal detachment and papillitis were observed in her both eyes. She also had neurological symptoms such as a headache. During the systemic treatment period, some of the side effects related to steroids emerged. Additionally, the symptoms and findings of the disease relapsed while the steroid dose was reduced. Conclusion. Early diagnosis and selection of an individualized appropriate treatment provided good clinical and visual results without any serious complications in our case.